Study of rain attenuation on a digital microwave radio link is Selangor (Malaysia) / Mohd. Jani Sapron - Sapron, Mohd. Jani (1993)
Rain effects play an important role in the overall system performance and microwave communication reliability of terrestrial systems for frequencies above 10 GHz. The magnitude of these effects depends on rain charateristic. Attenuation due to rainfall restricts the path length of microwave system and the use of -higher frequencies for line of sight communication. This project report presents results of the propagation and rainfall measurements undertaken in Petaling Jaya ( Selangor ). Data is based on two months (Aug.-Oct.) of simultaneous measurements of the signal level as well as rainfall rate on an 11.2 GHz, terrestrial link. The measured data are used to investigate the rainfall rate and its effects on the performance of the existing digital radio link.